The alteration of left ventricular strain in later-onset spinal muscular atrophy children - Cui, Yiqin; Feng, Yijie; Xia, Yu; Fu, Xingpeng; Gong, Ming; Qian, Jingjing; Yu, Jin; Ye, Jingjing; Gao, Feng; Cheng, Hongqiang; Mao, Shanshan (Frontiers in Cellular Neuroscience, 2022)
Background: Patients with spinal muscular atrophy (SMA) may suffer from multisystem injury, including an impaired cardiovascular system. However, M-mode echocardiography, the current dominant echocardiographic modality, is limited in the detection of myocardial injury. We considered the use of left ventricular strain imaging in detecting myocardial injury and explored the serum lipid profile related to cardiovascular disease in later-onset SMA children. Methods: A case-control study involving 80 patients with later-onset SMA and 80 age-, gender-, and body surface area-matched control children was conducted in a single tertiary pediatric hospital in China. Data on the left ventricular strain measured using two-dimensional speckle tracking echocardiography, left ventricular function parameters assessed by M-mode echocardiography, and serum lipid profile of these two groups were retrospectively collected for differential analysis. Results: The mean age of the 80 SMA patients were (6.87 ± 2.87) years, of which 46 were type 2 and 34 were type 3 patients. The global longitudinal strain (GLS) of the SMA group (-18.7 ± 2.9%, p<0.001) was lower than that of the control group; the time to peak longitudinal strain (TTPLS) of the SMA group (22.9 ± 13.6 ms, p<0.001) was higher than that of the control group, while left ventricular ejection fraction (LVEF) and left ventricular fractional shortening (LVFS), measured by the Teichholz method of M-mode echocardiography, showed no significant differences between the two groups. In addition, independent indicators for cardiovascular risk, including total cholesterol (TC)/HDL, low-density lipoprotein (LDL)/HDL, and Apo B/Apo A1 levels, were higher in SMA children than in the control group.